Acid-washed carbon-coated lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
By using acidic carbon-based materials and sintering procedures to optimize the structure during the pickling process, the poor circulation performance problem caused by excessive specific surface area of the positive electrode material after pickling is solved, and efficient and stable positive electrode material performance is achieved.
Patent Information
- Application Number
- CN202411529837.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, the specific surface area of the positive electrode material after pickling is too large, resulting in poor circulation performance.
Pickling solution containing acidic carbon-based materials is used for pickling, and the process of pickling and carbon coating is completed in one step, avoiding the steps of adding additives, and optimizing the structure through the sintering procedure to form a structure with a small surface specific surface area and a large internal specific surface area. .
It effectively improves the activation performance and capacity retention rate of the first circle of the cathode material, reduces the energy consumption and production steps of the material, and improves the cycle stability and battery capacity.
Smart Images

Figure BDA0005110215470000111 
Figure BDA0005110215470000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to an acid-washed carbon-coated lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art
[0002] Commonly used positive electrode materials for lithium-ion batteries include ternary positive electrode materials, lithium iron phosphate positive electrode materials and lithium-rich manganese-based positive electrode materials. Lithium-rich manganese-based positive electrode materials have the advantages of higher theoretical specific capacity and low price. Cobalt-free systems can be further used to reduce costs. However, the first-cycle activation performance and capacity of the prepared lithium-rich manganese-based positive electrode materials are worse than those of the cobalt system. Lithium-rich manganese-based positive electrode materials also have the problem of high residual alkali.
[0003] The residual alkali content of the positive electrode material is controlled by water washing, but the effect is limited and the speed is slow; the existing technology uses an acid washing process to reduce the residual alkali, which efficiently and quickly improves the first-cycle electrical performance of the positive electrode material and also increases the specific surface area of the positive electrode material. A large specific surface area will lead to poor cycle performance. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art that the positive electrode material has a large specific surface area after pickling, resulting in poor cycle performance, and thus provide an acid-washed carbon-coated lithium-rich manganese-based positive electrode material and a preparation method and application thereof. The preparation method does not require the addition of any additives after pickling, and the prepared acid-washed carbon-coated lithium-rich manganese-based positive electrode material has a carbon coating layer on the outside, a small specific surface area, energy saving, and simplified steps.
[0005] To this end, the present invention provides the following technical solutions.
[0006] The present invention provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material, comprising the following steps:
[0007] preparing a lithium-rich manganese-based precursor, acid washing, and sintering to obtain an acid-washed carbon-coated lithium-rich manganese-based positive electrode material;
[0008] The pickling is performed using a pickling solution; the pickling solution contains an acidic carbon-based material.
[0009] In an optional embodiment, the acidic carbon-based material includes at least one of acidic carbon quantum dots, acidic graphene and acidic carbon nanotubes.
[0010] In an optional embodiment, the concentration of the acidic carbon-based material in the pickling solution is 0.06-0.1 mol / L;
[0011] Preferably, the concentration of the acidic carbon-based material in the pickling solution is 0.07-0.09 mol / L;
[0012] In an optional embodiment, the pH value of the pickling solution is 4-5.
[0013] In an optional embodiment, the method for preparing the acidic carbon-based material comprises: mixing the carbon-based material and an acidic reagent;
[0014] Preferably, the acidic reagent includes at least one of sulfuric acid, hydrochloric acid, nitric acid, citric acid and acetic acid;
[0015] Preferably, the acidic reagent includes at least one of sulfuric acid, hydrochloric acid and nitric acid;
[0016] Preferably, the mass concentration of the sulfuric acid is 95-98%;
[0017] Preferably, the mass concentration of the nitric acid is 68-70%;
[0018] Preferably, the mass concentration of the hydrochloric acid is 35-37%;
[0019] Preferably, the mixing temperature is 60-100°C;
[0020] Preferably, the mixing time is 24-36h;
[0021] Preferably, the mixing speed is 600 rpm;
[0022] Preferably, the carbon-based material includes at least one of carbon quantum dots, graphene and carbon nanotubes.
[0023] Specifically, the acidic carbon quantum dot solution is prepared according to the conventional process in the art. As an example, the preparation steps of the acidic carbon quantum dot solution are as follows: a pure graphite rod is used as a carbon source and a working electrode, a platinum wire is used as a counter electrode, and ultrapure water is used as an electrolyte. The graphite rod and the platinum wire are immersed in ultrapure water and stirred continuously. The power supply is turned on and a voltage of 10-20V is applied. The reaction is continued for 10-15 days, and the volume is filtered to obtain a carbon quantum dot solution. The carbon quantum dot solution is mixed with sulfuric acid with a mass concentration of 95%, stirred at 60°C for 24h, and after the solution is cooled, it is centrifuged and washed with ultrapure water, and then ultrasonicated for 2h to evenly disperse the acidic carbon quantum dot solution to obtain a uniform acidic carbon quantum dot solution.
[0024] Specifically, the acidic carbon nanotube solution is prepared according to conventional processes in the art. As an example, the preparation steps of the acidic carbon nanotube solution are as follows: carbon nanotubes are prepared by chemical vapor deposition; the carbon nanotube solution and sulfuric acid with a mass concentration of 95% are mixed, stirred at 60°C for 24 hours, and after the solution is cooled, it is centrifuged and washed with ultrapure water, and then ultrasonicated for 2 hours to evenly disperse the acidic carbon nanotube solution to obtain a uniform acidic carbon nanotube solution.
[0025] Specifically, the acidic graphene solution is prepared according to conventional processes in the art. As an example, the preparation steps of the acidic graphene solution are as follows: graphene is prepared by chemical oxidation; graphene and sulfuric acid with a mass concentration of 95% are mixed, stirred at 60°C for 24 hours, and after the solution is cooled, it is centrifuged and washed with ultrapure water, and then ultrasonicated for 2 hours to evenly disperse the acidic graphene solution to obtain a uniform acidic graphene solution.
[0026] In an optional embodiment, the mass ratio of the lithium-rich manganese-based precursor to the pickling solution is 1:(4-8);
[0027] Preferably, the mass ratio of the lithium-rich manganese-based precursor to the pickling solution is 1:(5-7);
[0028] In an optional embodiment, the pickling time is 10-20min;
[0029] Preferably, the pickling time is 12-18 minutes.
[0030] During the pickling, the stirring speed is 400-600 rpm.
[0031] In an optional embodiment, the acid washing further includes suction filtration and drying;
[0032] Preferably, the filtration time is 20-40 min;
[0033] Preferably, the filtration pressure is -0.8 to -0.5 MPa;
[0034] Preferably, the drying temperature is 100-120°C;
[0035] Preferably, the drying time is 2-4 hours.
[0036] In an optional embodiment, the solution obtained by mixing the carbon-based material and the acidic solution is cooled and then washed;
[0037] Preferably, the washing solution comprises ultrapure water.
[0038] In an optional embodiment, the sintering temperature is 300-500°C;
[0039] In an optional embodiment, the sintering time is 4-6h;
[0040] In an optional embodiment, the heating rate of the sintering is 1-4°C / min;
[0041] In an optional embodiment, the sintering is performed in an oxygen-containing atmosphere.
[0042] In an optional embodiment, the specific steps of preparing the lithium-rich manganese-based precursor include: mixing the first precursor and the lithium salt, sintering at a high temperature, and sintering at a low temperature;
[0043] Preferably, the heating rate of sintering is 1-4°C / min;
[0044] Preferably, the cooling sintering rate is 1-2°C / min;
[0045] Preferably, the specific steps of the temperature-raising sintering include: raising the temperature to 650-750° C. and maintaining it for 6-10 hours, and then raising the temperature to 900-980° C. and maintaining it for 8-12 hours;
[0046] Preferably, the specific steps of the temperature reduction sintering include: cooling to 550-650° C. and maintaining for 0.5-2 h.
[0047] In an optional embodiment, the first precursor includes nickel manganese hydroxide;
[0048] In an optional embodiment, the lithium salt includes at least one of lithium carbonate and lithium hydroxide;
[0049] Preferably, the lithium salt is lithium carbonate;
[0050] In an optional embodiment, the ratio of the total molar amount of nickel element and manganese element in the first precursor to the molar amount of lithium element in the lithium salt is 1:(1.3-1.5);
[0051] In an optional embodiment, the preparation of the lithium-rich manganese-based precursor is carried out in an oxygen-containing atmosphere.
[0052] The present invention also provides an acid-washed carbon-coated lithium-rich manganese-based positive electrode material prepared by the above preparation method.
[0053] The present invention also provides an application of the acid-washed carbon-coated lithium-rich manganese-based positive electrode material prepared by the above preparation method in a lithium-ion battery.
[0054] The technical solution of the present invention has the following advantages:
[0055] 1. The preparation method of the pickled carbon-coated lithium-rich manganese-based positive electrode material provided by the present invention comprises the following steps: preparing a lithium-rich manganese-based precursor, pickling, sintering, and obtaining the pickled carbon-coated lithium-rich manganese-based positive electrode material; adopting a pickling solution for the pickling, and the pickling solution comprises an acidic carbon-based material. The present invention can complete pickling and carbon coating in one step by adopting a pickling solution containing an acidic carbon-based material for pickling. The method is simple, reduces energy consumption and time, simplifies the process steps, omits the step of adding additives after pickling, and overcomes the defect of the prior art that the cycle performance deteriorates due to the increase in specific surface area after pickling; on the one hand, pickling can effectively improve the first-cycle activation performance and first effect of the positive electrode material and reduce residual alkali; on the other hand, pickling can make the pickled carbon-coated lithium-rich manganese-based positive electrode material form a structure with a small surface specific surface area and a large internal specific surface area. The large internal specific surface area provides more pores and internal channels, which improves the diffusion of lithium ions Rate and reaction activity, small surface specific surface area can reduce side reactions, improve surface stability and structural stability, reduce the risk of pulverization when the material is compacted, extend the service life of the material, and improve cycle stability and capacity retention rate, avoiding the situation in the prior art where the positive electrode material is crushed when compacted due to excessive specific surface area; the large internal specific surface area of the positive electrode material also helps to increase the battery capacity, and the small surface specific surface area can improve the material stability. The present invention adopts a specific pickling process to improve the performance of the positive electrode material, which can make the capacity and cycle life more balanced, reduce external reactions, and improve the long-term stability and specific capacity of the positive electrode material. Therefore, the pickled carbon-coated lithium-rich manganese-based positive electrode material prepared by the present invention has a high discharge specific capacity, first efficiency and cycle retention rate.
[0056] 2. The preparation method of the acid-washed carbon-coated lithium-rich manganese-based positive electrode material provided by the present invention adopts a unique sintering procedure to obtain a lithium-rich manganese-based precursor, and the temperature is raised to 650-750°C and maintained for 6-10 hours, so that the first precursor and the lithium source can be fully diffused and mixed to initially form a crystalline phase. In this process, lithium ions will not volatilize in large quantities, thereby helping to form a layered structure later; the temperature is then raised to 900-980°C and maintained for 8-12 hours. During the sintering process, the initially formed crystalline phase further forms a stable layered structure, and the crystal grains grow to a suitable primary grain size, thereby improving the electrochemical performance; finally, the temperature is cooled to 550-650°C and maintained for 0.5-2 hours, thereby avoiding the thermal stress caused by directly cooling to room temperature and causing lattice distortion, reducing the stress within the particles and avoiding the formation of microcracks inside the material; the grain size can also be further controlled to obtain an ideal primary grain size. DETAILED DESCRIPTION
[0057] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0058] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0059] Example 1
[0060] This embodiment provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material, comprising the following steps:
[0061] (1) Ni 0.35 Mn 0.65 (OH )2 The total molar amount of nickel element and manganese element in lithium carbonate and the molar amount of lithium element in lithium carbonate are mixed in a high-speed mixer at a ratio of 1:1.4, and in an air atmosphere in a muffle furnace, the temperature is increased from room temperature to 700°C at a heating rate of 3°C / min and then maintained for 8 hours, and then increased to 940°C and maintained for 10 hours; the temperature is reduced to 600°C at a cooling rate of 1°C / min and then maintained for 1 hour, and then naturally cooled to room temperature to obtain a lithium-rich manganese-based precursor;
[0062] (2) Preparation of acidic carbon quantum dot solution: using pure graphite rod as carbon source and working electrode, platinum wire as counter electrode, ultrapure water as electrolyte, immersing graphite rod and platinum wire in ultrapure water, and stirring continuously, connecting power supply to apply voltage of 20V, continuing reaction for 10 days, filtering and fixing volume, and obtaining pure carbon quantum dot solution; mixing pure carbon quantum dot solution with sulfuric acid with mass concentration of 95%, stirring at 60°C for 24h, cooling and washing with ultrapure water by centrifugation, ultrasonicating for 2h, and power of 300W, and obtaining acidic carbon quantum dot solution;
[0063] (3) The lithium-rich manganese-based precursor and the acidic carbon quantum dot solution were acid-washed by stirring at 450 rpm for 15 min, then filtered at -0.8 MPa for 30 min, placed in a vacuum oven for drying at 120°C for 2 h, heated from room temperature to 400°C at a heating rate of 3°C / min in an air atmosphere, and then sintered for 5 h, and naturally cooled to room temperature to obtain an acid-washed carbon-coated lithium-rich manganese-based positive electrode material. Among them, the mass ratio of the lithium-rich manganese-based precursor and the acidic carbon quantum dot solution is 1:6; the concentration of the acidic carbon quantum dot solution is 0.08 mol / L, and the pH value is 4-5.
[0064] Example 2
[0065] This embodiment provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (3), the mass ratio of the lithium-rich manganese-based precursor to the acidic carbon quantum dot solution is 1:4.
[0066] Example 3
[0067] This embodiment provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (3), the mass ratio of the lithium-rich manganese-based precursor to the acidic carbon quantum dot solution is 1:8.
[0068] Example 4
[0069] This embodiment provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (3), the acid washing time is 10 minutes.
[0070] Example 5
[0071] This embodiment provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (3), the acid washing time is 20 minutes.
[0072] Example 6
[0073] This embodiment provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (3), the concentration of the acidic carbon quantum dot solution is 0.06 mol / L, instead of the concentration of the acidic carbon quantum dot solution in Example 1 being 0.08 mol / L.
[0074] Example 7
[0075] This embodiment provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (3), the concentration of the acidic carbon quantum dot solution is 0.1 mol / L, instead of the concentration of the acidic carbon quantum dot solution in Example 1 being 0.08 mol / L.
[0076] Example 8
[0077] This embodiment provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material, comprising the following steps:
[0078] (1) Ni 0.35 Mn 0.65 (OH )2The total molar amount of nickel element and manganese element in lithium hydroxide and the molar amount of lithium element in lithium hydroxide are mixed in a high-speed mixer at a ratio of 1:1.3, and in an air atmosphere in a muffle furnace, the temperature is increased from room temperature to 650°C at a heating rate of 1°C / min and then maintained for 6 hours, and then increased to 900°C and maintained for 8 hours; the temperature is reduced to 650°C at a cooling rate of 2°C / min and then maintained for 2 hours, and then naturally cooled to room temperature to obtain a lithium-rich manganese-based precursor;
[0079] (2) Preparation of acidic carbon nanotube solution: Carbon nanotubes were prepared by chemical vapor deposition; carbon nanotubes were mixed with nitric acid having a mass concentration of 68%, stirred at 100° C. for 35 h, cooled, centrifuged and washed with ultrapure water, and ultrasonicated for 2 h at a power of 300 W to obtain an acidic carbon nanotube solution;
[0080] (3) The lithium-rich manganese-based precursor and the acidic carbon nanotube solution were stirred at 600 rpm for 15 minutes, then filtered at -0.5 MPa for 20 minutes, placed in a vacuum oven at 100°C for 4 hours, heated from room temperature to 500°C at a heating rate of 1°C / min in an air atmosphere, and then sintered for 6 hours, and naturally cooled to room temperature to obtain an acid-washed carbon-coated lithium-rich manganese-based positive electrode material. The mass ratio of the lithium-rich manganese-based precursor to the acidic carbon nanotube solution was 1:6; the concentration of the acidic carbon nanotube solution was 0.08 mol / L, and the pH value was 4-5.
[0081] Example 9
[0082] This embodiment provides a method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material, comprising the following steps:
[0083] (1) Ni 0.35 Mn 0.65 (OH )2 The total molar amount of nickel element and manganese element in lithium carbonate and the molar amount of lithium element in lithium carbonate are mixed in a high-speed mixer at a ratio of 1:1.5, and in an air atmosphere in a muffle furnace, the temperature is increased from room temperature to 750°C at a heating rate of 4°C / min, and then maintained for 8 hours, and then increased to 980°C and maintained for 10 hours; the temperature is reduced to 550°C at a cooling rate of 1°C / min, and then maintained for 1.5 hours, and then naturally cooled to room temperature to obtain a lithium-rich manganese-based precursor;
[0084] (2) Preparation of acidic graphene solution: Graphene was prepared by chemical oxidation method; graphene was mixed with hydrochloric acid with a mass concentration of 36%, stirred at 80° C. for 30 h, cooled, centrifuged and washed with ultrapure water, and ultrasonicated for 2 h at a power of 300 W to obtain an acidic graphene solution;
[0085] (3) The lithium-rich manganese-based precursor and the acidic graphene solution were stirred at 500 rpm for 10 minutes for acid washing, then filtered at -0.7 MPa for 40 minutes, placed in a vacuum oven for drying at 100°C for 4 hours, heated from room temperature to 300°C at a heating rate of 4°C / min in an air atmosphere, and then sintered for 4 hours, and naturally cooled to room temperature to obtain an acid-washed carbon-coated lithium-rich manganese-based positive electrode material. Among them, the mass ratio of the lithium-rich manganese-based precursor and the acidic graphene solution is 1:6; the concentration of the acidic graphene solution is 0.08 mol / L, and the pH value is 4-5.
[0086] Comparative Example 1
[0087] This comparative example provides a method for preparing a lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that the step (3) uses water washing instead of acid washing, which is as follows:
[0088] The lithium-rich manganese-based precursor and pure water were stirred at 450 rpm for 15 min, then filtered at -0.8 MPa for 30 min, placed in a vacuum oven and dried at 120°C for 2 h, heated from room temperature to 400°C at a heating rate of 3°C / min in an air atmosphere, sintered for 5 h, and naturally cooled to room temperature to obtain a lithium-rich manganese-based positive electrode material.
[0089] Comparative Example 2
[0090] This comparative example provides a method for preparing a lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (3), 0.08 mol / L oxalic acid solution is used instead of 0.08 mol / L acidic carbon quantum dot solution for acid washing.
[0091] Comparative Example 3
[0092] This comparative example provides a method for preparing a lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that step (3) is different. The specific steps of step (3) of this comparative example are as follows:
[0093] (3) The lithium-rich manganese-based precursor and oxalic acid solution were stirred at 450 rpm for 15 min, then filtered at -0.8 MPa for 30 min, placed in a vacuum oven at 120 ° C for 2 h, the dried product was mixed with carbon quantum powder, heated from room temperature to 400 ° C at a heating rate of 3 ° C / min in an air atmosphere, and then sintered for 5 h, and naturally cooled to room temperature to obtain a lithium-rich manganese-based positive electrode material. The mass ratio of the lithium-rich manganese-based precursor and the oxalic acid solution is 1:6; the concentration of the oxalic acid solution is 0.08 mol / L; the mass ratio of the dried product and the carbon quantum powder is 28.4:1.
[0094] Test Case
[0095] The performance tests of the lithium-rich manganese-based positive electrode materials prepared in the above examples and comparative examples are as follows:
[0096] Using N-methylpyrrolidone as a dispersant, lithium-rich manganese-based positive electrode material: carbon black: PVDF (polyvinylidene fluoride) were mixed at a mass ratio of 80:10:10 to prepare a positive electrode slurry, which was evenly coated on a carbon-coated aluminum foil with a coating surface density of 3 cm 2 / mg, and dried in an oven at 80°C for 2h to obtain a positive electrode sheet; in an argon atmosphere in a glove box, a Celgard 2500 separator and a lithium metal sheet were used as the negative electrode sheet, and the electrolyte was 1 mol / L (EC, EMC and DMC in a volume ratio of 1:1:1); a CR2032 button half-cell was assembled in the order of negative electrode sheet, electrolyte, separator, electrolyte and positive electrode sheet.
[0097] The performance of the battery prepared above and the lithium-rich manganese-based composite electrode of the comparative example were tested as follows:
[0098] (1) Residual alkali detection method: GB / T 11064.1-2013 Chemical analysis method for lithium carbonate, lithium hydroxide monohydrate and lithium chloride shall be used for detection.
[0099] (2) Specific surface area detection method: GBT19587-2017 Determination of specific surface area of solid substances by gas adsorption BET method is used for detection.
[0100] (3) 0.2C discharge specific capacity test method: At 25°C, the battery is charged at 0.2C and discharged once at 0.2C. The results are shown in Table 1. The first efficiency calculation formula is as follows:
[0101] First effect = 100% × 1 st Discharge specific capacity / 1 st Charge capacity
[0102] (4) Cycle performance test method: At 25°C, the battery was charged at 0.2C, discharged once at 0.2C, and cycled 52 times. The results are shown in Table 1. The cycle performance calculation formula is as follows:
[0103] Cycle performance = 100% × 52 th Discharge specific capacity / 3 rd Discharge specific capacity
[0104] Table 1 Performance results of various embodiments and comparative examples
[0105]
[0106]
[0107] As can be seen from Table 1, the acid-washed carbon-coated lithium-rich manganese-based positive electrode material prepared in the present invention has a small specific surface area, a high 0.2C discharge specific capacity, a high first efficiency, and good cycle performance.
[0108] Comparing Example 1 with Comparative Example 1, the comparative example 1 without acid washing has high residual alkali, small specific surface area, and obvious decreases in 0.2C discharge specific capacity, first efficiency, and cycle performance.
[0109] By comparison between Example 1 and Comparative Example 2, although the use of oxalic acid solution instead of the carbon-based pickling solution for pickling can reduce the residual alkali, the surface specific surface area of the material is too large, and the 0.2C discharge specific capacity, first efficiency and cycle performance of the pickled carbon-coated lithium-rich manganese-based positive electrode material prepared by the preparation method of the present invention are not as high.
[0110] Comparing Example 1 with Comparative Example 3, Comparative Example 3 needs to be acid-washed first, and then carbon quantum powder is added for thorough mixing and sintering, and the steps are complicated. It is not as energy-saving as the present invention, and the steps are simple. In addition, the positive electrode material obtained has less residual alkali and a higher battery capacity.
[0111] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing an acid-washed carbon-coated lithium-rich manganese-based positive electrode material, characterized in that: The steps include: preparing a lithium-rich manganese-based precursor, acid washing, and sintering to obtain an acid-washed carbon-coated lithium-rich manganese-based positive electrode material; The pickling is performed using a pickling solution; the pickling solution contains an acidic carbon-based material.
2. The preparation method according to claim 1, characterized in that: The acidic carbon-based material includes at least one of acidic carbon quantum dots, acidic graphene and acidic carbon nanotubes.
3. The preparation method according to claim 2, characterized in that: The concentration of the acidic carbon-based material in the pickling solution is 0.06-0.1 mol / L; and / or, The pH value of the pickling solution is 4-5.
4. The preparation method according to claim 1, characterized in that: The method for preparing the acidic carbon-based material comprises: mixing the carbon-based material and an acidic reagent; Preferably, the acidic reagent includes at least one of sulfuric acid, hydrochloric acid, nitric acid, citric acid and acetic acid; Preferably, the mixing temperature is 60-100°C; Preferably, the mixing time is 24-36 hours.
5. The preparation method according to claim 3, characterized in that: The mass ratio of the lithium-rich manganese-based precursor to the pickling solution is 1:(4-8); and / or, The pickling time is 10-20 minutes.
6. The preparation method according to claim 1, characterized in that: The sintering temperature is 300-500°C; and / or, The sintering time is 4-6 hours; and / or, The heating rate of the sintering is 1-4°C / min; and / or, The sintering is performed in an oxygen-containing atmosphere.
7. The preparation method according to claim 1, characterized in that: The specific steps of preparing the lithium-rich manganese-based precursor include: mixing the first precursor and the lithium salt, sintering at a high temperature, and sintering at a low temperature; Preferably, the heating rate of sintering is 1-4°C / min; Preferably, the cooling sintering rate is 1-2°C / min; Preferably, the specific steps of the temperature-raising sintering include: raising the temperature to 650-750° C. and maintaining it for 6-10 hours, and then raising the temperature to 900-980° C. and maintaining it for 8-12 hours; Preferably, the specific steps of the temperature reduction sintering include: cooling to 550-650° C. and maintaining for 0.5-2 h.
8. The preparation method according to claim 7, characterized in that: The first precursor includes nickel manganese hydroxide; and / or, The lithium salt comprises at least one of lithium carbonate and lithium hydroxide; and / or, The ratio of the total molar amount of nickel element and manganese element in the first precursor to the molar amount of lithium element in the lithium salt is 1:(1.3-1.5); and / or, The preparation of the lithium-rich manganese-based precursor is carried out in an oxygen-containing atmosphere.
9. Acid-washed carbon-coated lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the acid-washed carbon-coated lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 8 in lithium-ion batteries.
Citation Information
Cited By
Cation-doped lithium-rich manganese-based positive electrode material, preparation method thereof and battery
CN122511819A